Correlation between PEAK relational training system and one-word picture vocabulary tests. (April 2015) - McKeel, Autumn; Rowsey, Kyle; Dixon, Mark R.; Daar, Jacob H.
Highlights: Twenty seven children with autism or related intellectual disabilities completed the PEAK: direct training module, the EOWPVT-4 and the ROWPVT-4. Statistically significant correlations were found between PEAK and both OWPVT-4 assessments. PEAK scores were found to be highly reliable across multiple assessors. Abstract: The past few decades of research in autism spectrum disorders have been successful in developing effective behavioral treatments; however, the psychometrics of these strategies has not been documented well in applied settings. The current experiment evaluated the relationship between established measures of language skills (receptive and expressive one-word picture vocabulary test; ROWPVT-4 and EOWPVT-4, respectively) and a recently released assessment and curriculum tool designed to teach instructional skills using a behavior analytic approach (promoting the emergence of advanced knowledge relational training system; PEAK). Each participant was administered three assessments: The PEAK direct training module assessment, the ROWPVT-4 assessment, and the EOWPVT-4 assessment. Scores from all three assessments were compared to assess the relationship between each assessment. The results indicated both a strong correlation between the PEAK direct training module and commonly used language assessments (ROWPVT-4 and EOWPVT-4), as well as strong reliability in the administration of the assessments.